KEPUASAN KONSUMEN TERHADAP KUALITAS KULINER LOKAL MIE SAGU PADA UMKM DI KOTA PEKANBARU - Hamidi, Wahyu; Elida, Septina; Vaulina, Sisca; Khairizal, Khairizal (Jurnal Daya Saing, 2023)
Sago noodles are a local culinary dish made from sago. The presence of sago noodles will enrich the culinary treasures of Riau. This research aims to analyze consumer satisfaction with the culinary quality of sago noodles in Pekanbaru City. The sampling technique used nonprobability sampling followed by a judgment sampling method for 100 consumers who were purchasing sago noodles as respondents. Data were analyzed using descriptive analysis methods, Important Performance Analysis (IPA), and Customer Statistics Index (CSI). The results of the Important Performance Analysis (IPA) research show that there are still several things that do not meet consumer expectations. The attributes that are the main priority in improving performance and to be improved are the sago noodle topping and serving speed. Several attributes are in a position to be maintained, namely taste, uniqueness, completeness of sago noodles, guarantee, maturity, product variety, appearance, price, and portion. Based on the calculation of the consumer satisfaction index (CSI) value for local sago noodle culinary, it is 62.46%, in the range of 0.50-0.66, meaning that consumers are quite satisfied with the level of attribute performance in local sago noodle culinary.